2011
DOI: 10.2527/jas.2010-3175
|View full text |Cite
|
Sign up to set email alerts
|

Developmental factors that influence sow longevity1

Abstract: The length of adult sow life is now recognized as both an economic and a welfare concern. However, there are no consistent definitions to measure sow longevity. This study assessed 6 different descriptions of longevity and determined their relationship with developmental performance factors. Longevity definitions included stayability (probability of a sow producing 40 pigs or probability of her reaching 4 parities), lifespan (number of parities a female has accumulated before culling), lifetime prolificacy (nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
70
4
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(83 citation statements)
references
References 21 publications
7
70
4
2
Order By: Relevance
“…However, they are higher than values (34.9 and 38.5 piglets) reported in the USA by Hoge and Bates (2011) and Nikkilä et al (2013)). The means for LKF, in this study, are lower than those found in Thailand by Noppibool et al (2013) in Landrace (89.8 kg) and Yorkshire sows (88.2 kg).…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…However, they are higher than values (34.9 and 38.5 piglets) reported in the USA by Hoge and Bates (2011) and Nikkilä et al (2013)). The means for LKF, in this study, are lower than those found in Thailand by Noppibool et al (2013) in Landrace (89.8 kg) and Yorkshire sows (88.2 kg).…”
Section: Discussioncontrasting
confidence: 59%
“…However, some studies report the lack of significant effect of age at first farrowing on lifetime productivity (López and Galíndez 2011a, b;Noppibool et al 2013). Furthermore, there are some reports on the effect of litter size at first farrowing on lifetime productivity at farrowing and at weaning (Hoge and Bates 2011;Sobczynska et al 2013). Lifetime productivity estimates and factors affecting them, under the conditions of Mexico and particularly of the Mexican tropics, have not been reported, except of a study on the length of productive life of sows in the herd (Segura-Correa et al 2011a).…”
Section: Introductionmentioning
confidence: 93%
“…Fast growth rate increased culling risk in previously published work involving Yorkshire sows (Yazdi et al, 2000a;Hoge and Bates, 2011), but such effect was not observed in Swedish Landrace (Yazdi et al, 2000b). Knauer et al (2010) reported negative regression coeffi cients for stayability on ADG in crossbred maternal lines.…”
Section: Genetic Correlationsmentioning
confidence: 88%
“…Along these assumptions, as maternal line females, gilts from the current population may have had suffi cient backfat and therefore antagonistic associations remained weak in the quantitative analyses. Yazdi et al (2000a) and Hoge and Bates (2011) reported that Yorkshire females with greater backfat thickness experienced a decreased culling risk, but according to Yazdi et al (2000b) side-fat thickness was not associated with risk of culling in Swedish Landrace sows. Fernàndez de Sevilla et al (2008) found low backfat thickness increasing risk of culling in Spanish Landrace but not in Large White sows.…”
Section: Genetic Correlationsmentioning
confidence: 99%
See 1 more Smart Citation